The Integration of Core Value “AKHLAK” into Business Strategy of Prophet Muhammad - Muh Shadiqul Fajri AF; Swadia Gandhi Mahardika; Akbar Lufi Zulfikar; Abiyajid Bustami; Swadia Indra Maulana (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
Core Value is the soul of an organization or institution. The Ministry of State-Owned Enterprises has established AKHLAK as a core value in working well and correctly to build the nation. AKHLAK is an acronym for Amanah, Kompeten, Harmoni, Loyal, Adaptif, and Kolaboratif. The aim of this research is to determine the relationship between the core value of AKHLAK and the business strategy implemented by the Prophet Muhammad SAW. This type of research is descriptive qualitative using the library research method. The main data sources for this research were obtained from books and articles published in the last 10 (ten) years in journals that are accredited both nationally and internationally. The results of the research show that the core value of AKHLAK is related to the business strategy of the Prophet Muhammad SAW, keeping promises and telling the truth about the products (Amanah), learning to do business from the age of 12 (twelve) years (Kompeten), without badmouthing other people's businesses who are competitors and paying employee wages before the sweat dries (Harmoni), obeying the leadership's orders as long as they do not conflict with the Shari'a (Loyal), understanding market needs (Adaptif), building strong relationships with various tribes (Kolaboratif).